Post-World War II Italian school buildings: typical and specific seismic vulnerabilities. (December 2015) - Clementi, F.; Quagliarini, E.; Maracchini, G.; Lenci, S.
Abstract: Structures belonging to the same type and built in the same period may share similar geometrical and spatial characteristics. When these features also affect the seismic response of the buildings, they are referred to as typical seismic vulnerabilities. When a building presents one or more of these typical vulnerabilities, some general and qualitative considerations on its seismic behaviour can be made a priori, considering their actual influence on the seismic behaviour of other similar cases. In this work, we propose and apply a specific procedure based on a priori considerations to a specific building type: the post-World War II Italian Schools. To this purpose, we first improved our knowledge about this type of building, pointing out typical and specific seismic vulnerabilities by studying the standard architectural principles suggested by the main manuals and laws of that time. Then, in order to find how these typological features affect the global seismic behaviour of the examined structures, we analysed a real case study representative of the entire building type. Pushover and Nonlinear Dynamic analyses have been carried out, considering four different models, representing three different configurations that may result from different combinations of the most significant typical vulnerabilities. The result of this work confirms that in the case of post-World War II Italian school buildings, typological vulnerabilities such as wide atriums, eccentric stairs and tall windows, along with irregularity in plan configuration, can strongly affect the global seismic behaviour of the school buildings. Highlights: A Post-World War II Italian School Building typology was defined from coeval literature. New typical and specific seismic vulnerabilities were identified for this building typology. A relevant case study was recognised inside a large scale of seismic vulnerability assessment of these types of structures. The effective influence of these vulnerabilities on its seismic behaviour has been quantified with nonlinear static and nonlinear incremental dynamic analyses. The knowledge of these outcomes may help professional engineers and architects in designing suitable interventions.